Stratigraphy and Petrography of the Jutana Dolomite, Khewra Gorge, Khewra, Jehlum district; Punjab, Pakistan - Khan, Muhammad Attaullah; Khan, M. Javed; Alizai, Saeed Akhtar Khan (Journal of Himalayan Earth Sciences, 1977)
This paper presents a detailed study of the Jutana Dolomite, exposed in the Khewra Gorge, Salt Range; Pakistan. The work consists of detailed study of stratigraphy and petrogarphy of the Jutana Dolomite. Environments of deposition with reference to the above mentioned salient features are also elaborately discussed. The Jutana Dolomite was deposited under calm, warm, shallow, and well-oxygenated marine environments. Nevertheless, a part of it was definitely deposited under slightly agitated conditions. Such episodes are indicated by occurrence of oolitic/pisolitic structures in strata exposed at several stratigraphic levels. On the basis of lithology, petrography, and sedimentary structures, the Jutana Dolomite is divisible into three distinct units. This division is particularly very sharp in the Khewra Gorge. The divisions, as recognized in the Khewra Gorge, in order of superposition are: Upper Dolomite …………………… Thick bedded pure dolomite. Middle Shale ……………………Bluish-gray, maroon, and purple shale. Lower Dolomite……………………Thin bedded, arenaceous, argillaceous, and with oolitic/pisolitic bands at several stratigraphic levels. The Middle Shale unit is fossiliferous find contains dIn0st identical faunas as in the Middle shale member of the Khussak Formation. On the basis of these faunas, the Jutana Dolomite is assigned a Late Early Cambrian and is correlated with the dolomite outcrops exposed in the Trans-Indus Ranges, i,e., Khisor Range(west of Indus-Saiduwali) and on the eastern side of the Nilawahan Ravine. Petrographic studies revealed that the Jutana dolomite is dominantly composed of carbonates (dolomite/calcite), sandy-dolomite, and dolomitic/calcareous sandstones The dominant minerals present other than carbonates are, quartz, micas, chlorite, and glauconite.